Atuação dos orientadores pedagógicos dos centros de educação infantil do município de Sorocaba - Galão, Sabrina Aparecida (Universidade Federal de São Carlos, 2022)
This study aimed to investigate the role of the Pedagogical Advisor who works in the public network in Early Childhood Education institutions in a city in the interior of São Paulo. As specific objectives were defined: 1) to know the Pedagogical Advisor's perspective regarding his/her professional role; 2) to investigate the challenges, potentialities and characteristics of the work and significant experiences about the performance in the area. The research was based on the Cultural-Historical Theory and semi-structured interviews were carried out with 5 (five) Pedagogical Advisors effective in the position for more than five years. The information obtained indicates that the participants addressed the relevance of this professional's work and presented several dimensions about their role in Early Childhood Education, covering actions aimed at planning; the teaching-learning process and the training of teachers and education assistants. Challenges highlighted include: gaps in initial training; lack of continuing education; performance in two school units and various activities that extrapolate the functions related to the Pedagogical Advisor. The potential of the work involves the configuration of a school environment more favorable to the observation of child development, based on the pedagogical strategies carried out by the teachers; the training of educators and the existence of pedagogical actions that are more integrated with school agents. Regarding the experiences, it was observed that the participants exposed important events in their professional trajectories, based on the interrelation of social, cognitive and affective aspects. It is argued that, due to the complexity that permeates the reality of the Pedagogical Advisor's performance, it is understood that it is necessary to value this and other professionals in Education, especially in Early Childhood Education, from the recognition of the work of the Pedagogical Advisor. Pedagogical Advisor, aiming at the quality of care offered to early childhood.
Actuación de asesores pedagógicos de centros de educación infantil del municipio de Sorocaba
Keywords: Atuação; Coordenação pedagógica; Educação infantil; Performance; Pedagogical coordination; Early childhood education; CIENCIAS HUMANAS::EDUCACAO